Design and Implementation of a Modern Standard Marine Communication Phrases (SMCP) Language Learning Application - Ghadri, Mirco; Omar, Zakariya (My University, 2023)
This Bachelor’s thesis describes the development of a modern and updated Standard Marine Communication Phrases (SMCP) language learning application for the shipping and marine technology division at Chalmers University of Technology. The aim of this project is to design and construct a functional demo application that serves as a proof of concept and provides valuable insights for future development. By conducting data gathering, iterative design prototyping, and software implementation, the project successfully accomplished its goals. The outcomes include the identification of user needs and the creation and evaluation of a design prototype. Online surveys were utilized for data gathering and evaluation, allowing for the collection of user feedback and insights. The project resulted in the development of a fully functional cross-platform application compatible with Web, iOS, and Android platforms. The evaluation process validated the effectiveness of the design, while also highlighting potential areas for future enhancement. Ultimately the project’s findings and insights have the potential to significantly impact SMCP learning at Chalmers University of Technology and beyond.
Keywords: Standard Marine Communication Phrases (SMCP); Language Learning Application; Ship Communication; Cross-platform Application; User-centered Design; Software Development